Analisis Laba Kotor terhadap Profitabilitas pada Bank Tabungan Negara (BTN) - Tiara Maharani; Krisna Dwi Namduga; Danik Firdania; Renny Oktaviani (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research focuses on the Analysis of Gross Profit on the Profitability of the Bank Tabungan Negara. (BTN). The objective is to evaluate the rate of profitability of this BTN Bank from one period to the following periods, in 2019 to 2023. The data used in this study is secondary data obtained with the method of library study. The results obtained from this study show that the gross profits held by the Bank Tabungan Negara are categorized as normal or healthy.